Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises: 38

Answer

$y=2$ or $y=-3$

Work Step by Step

$y^{2}+y-6$ =$y^{2} + 3y - 2y -6$ =$y(y+3)-2(y+3)$ =$(y-2)(y+3)$ $y=2$ or $y=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.